The Influence of Socioeconomic Conditions on the Healthy Life Behavior - Br Sebayang, Lesta Karolina; Budi, Erika Rizqiyana; Janah, Ilma Ulfatul (JEJAK: Jurnal Ekonomi dan Kebijakan, 2017)
The purpose of this research is to find out the influence of economic, social and availability of information variable on the healthy life behavior of the people in Suruh Sub-district, Semarang Regency. The primary data source is collected by distributing the questionnaires to and by interviewing the people of Suruh Sub-district, Semarang Regency as the research respondents with the research analytical instrument of Probit binary responses regression. The availability of domestic wastewater disposal facilities is the dependent variable, while the household expenditure (economic variable), healthy life motivation (social variable) and maintenance of domestic wastewater disposal system (healthy life behavior) are the independent variables. The results show that the healthy life motivation and maintenance of domestic wastewater disposal system variables have positive and significant influence on the availability of domestic wastewater disposal facilities with ? = 5% and the household expenditure variable has positive and significant influence with ? = 10%. In general, it shows that the economic variable and the household expenditure determine the availability of domestic wastewater disposal facilities in Suruh Sub-district, Semarang Regency as the higher the individual’s income, the higher their allocation to the household expenditure, including to the domestic wastewater management.